(untitled) - Dugopolski, Mark (Boston Burr Ridge, Ill., 2006)
With a strong emphasis on skill-building, applications in the real world, and preparation for further math courses, this text unites the concepts of Elementary Algebra and Intermediate Algebra in one convenient and economical volume
Keywords: Algebra,Số học